Manufacturing consent Noam Chomsky and the media - Achbar, Mark.; Wintonick, Peter; British Film Institute (London : British Film Institute, 2009)
Explores the political life and times of the controversial author, linguist and radical philosopher, Noam Chomsky. Highlighting his analysis of media, Chomsky focuses on democratic societies where populations not disciplined by force are subject to more subtle forms of ideological control.
Producers, Peter Wintonick, Mark Achbar, Adam Symansky.
Keywords: Chomsky, Noam; Mass media criticism -- United States; Press and politics; Public opinion -- United States